2007
DOI: 10.2478/s11756-007-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrates along the Serbian section of the Danube River (stream km 1429–925)

Abstract: Abstract:Results of the investigation of the aquatic macroinvertebrate fauna along a 504 km stretch of the Danube River in Serbia are presented. A total of 74 macroinvertebrate taxa were observed during a 2001 survey. Oligochaeta and Mollusca were the principal components of the community with regard to species richness and abundance. Based on data on the qualitative composition of the macroinvertebrate fauna, a correspondence analysis divided the investigated stretch in three sectors -upper (Pannonian), Iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 7 publications
2
20
2
1
Order By: Relevance
“…The lower number of taxa detected during the present study in comparison to the 2001 Danube survey (when Paunovic et al 2007 reported 74 macroinvertebrate taxa), could be due to the lower number of sampling sites within the same stretch.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…The lower number of taxa detected during the present study in comparison to the 2001 Danube survey (when Paunovic et al 2007 reported 74 macroinvertebrate taxa), could be due to the lower number of sampling sites within the same stretch.…”
Section: Discussioncontrasting
confidence: 39%
“…Differences in the dominant sediment types between the Slovakian and Serbian stretches could be the main reason for the observed differences. The Slovakian sector is distinguished by a higher proportion of habitats with gravel, boulders and stones (Elexová 1998), while the Serbian part (Paunovic et al 2007) is predominantly characterized Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations